2020
DOI: 10.1002/1348-9585.12142
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene and trichloroethanol induce skin sensitization with focal hepatic necrosis in guinea pigs

Abstract: Objectives Occupational exposure to trichloroethylene (TCE) induces trichloroethylene hypersensitivity syndrome (TCEHS), which causes hypersensitivity dermatitis and hepatitis. However, whether TCE itself or its two metabolites, trichloroethanol (TCEOH) and trichloroacetic acid (TCA), are involved in TCEHS remains unclear. Therefore, in this study we explored the allergens causing TCEHS and characterized TCEHS‐related liver injury in guinea pigs. Method The guinea pig m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Skin allergy test of EK1 was performed on a guinea pig model as described. 44 Briefly, forty guinea pigs were randomly divided into vehicle control group, DNCB-treatment group, and EK1-treated group (4.0 mg/kg). Sensitization was carried out on the depilated area of left back three times on the 0th, 7th, and 14th day.…”
Section: Methodsmentioning
confidence: 99%
“…Skin allergy test of EK1 was performed on a guinea pig model as described. 44 Briefly, forty guinea pigs were randomly divided into vehicle control group, DNCB-treatment group, and EK1-treated group (4.0 mg/kg). Sensitization was carried out on the depilated area of left back three times on the 0th, 7th, and 14th day.…”
Section: Methodsmentioning
confidence: 99%
“…TCE was used primarily as an industrial solvent for the cleaning and degreasing of metals due to its good skim and decontamination properties (Dumas et al, 2018), which induced OMDT in partial occupational workers. The vast majority of OMDT patients present liver injury (Zhao et al, 2020) and animal experiments also reveal that TCE causes liver damage in mice. Liver macrophages play an important role in the liver pathophysiology, previous studies demonstrated that liver inflammation is linked to metabolic signals such as TNF‐α that induce cellular stress responses in liver macrophages including polarization and autophagy (Sun et al, 2020; Wang, Che, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who survive after high-dose glucocorticoid treatment are also often accompanied by multiple complications, such as hyperlipidemia, infection, and femoral head necrosis, and they can easily relapse. Due to its severity, OMDT has become one of the critical but unresolved issues in the field of dermatology and occupational health ( 7 ).…”
Section: Introductionmentioning
confidence: 99%